2007
DOI: 10.1115/1.2786529
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Predictive Capabilities of Detached Eddy Simulation to Simulate Flow and Mass Transport Past Open Cavities

Abstract: The three-dimensional (3D) incompressible flow past an open cavity in a channel is predicted using the Spalart–Almaras (SA) and the shear-stress-transport model (SST) based versions of detached eddy simulation (DES). The flow upstream of the cavity is fully turbulent. In the baseline case the length to depth (L∕D) ratio of the cavity is 2 and the Reynolds number ReD=3360. Unsteady RANS (URANS) is performed to better estimate the performance of DES using the same code and meshes employed in DES. The capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…The interest in LES and hybrid RANS-LES methods like detached eddy simulation (DES) is mainly motivated by their greater accuracy over RANS for flows dominated by large-scale unsteady coherent structures and massive separation. (e.g., see results of a combined RANS, DES and LES study of flow and ejection of contaminant from bottom river cavities reported in [3], [4] and [5]). Such 3D simulations provide the full mean and instantaneous flow fields, as well as the distribution of the turbulence fluctuations and the bed shear stress.…”
Section: Review Of Relevant Experimental and Numerical Studiesmentioning
confidence: 95%
“…The interest in LES and hybrid RANS-LES methods like detached eddy simulation (DES) is mainly motivated by their greater accuracy over RANS for flows dominated by large-scale unsteady coherent structures and massive separation. (e.g., see results of a combined RANS, DES and LES study of flow and ejection of contaminant from bottom river cavities reported in [3], [4] and [5]). Such 3D simulations provide the full mean and instantaneous flow fields, as well as the distribution of the turbulence fluctuations and the bed shear stress.…”
Section: Review Of Relevant Experimental and Numerical Studiesmentioning
confidence: 95%
“… Constantinescu and Squires [2003, 2004], Constantinescu et al [2003], and Chang et al [2007] discuss results of grid sensitivity and validation studies for simulations of the flow past spheres and channel flow over a bottom cavity conducted using the same code. In particular, Chang et al [2007] showed that the agreement between highly resolved LES and DES conducted on a much coarser mesh improved significantly when the inflow contained turbulent fluctuations obtained from a preliminary straight channel flow calculation. This is the approach adopted in the present study.…”
Section: Numerical Methods and Simulation Set Upmentioning
confidence: 99%
“…Detailed grid sensitivity and validation studies for the flow past spheres and for flow and contaminant transport in a channel with a bottom cavity are discussed in the work of Constantinescu and Squires [2003, 2004], Constantinescu et al [2003], and Chang et al [2007]. An additional validation test case was conducted for the case of a relatively low‐Reynolds‐number flow (Re = 18,000) past a circular cylinder mounted on a flat‐bed channel.…”
Section: Methodsmentioning
confidence: 99%
“…For internal flows (e.g., flow past surface‐mounted bodies in a channel) the predictions of DES in terms of the large‐scale eddy content, their dynamics, and the prediction of the mean flow and turbulence statistics are dependent on the presence, or not, of resolved turbulence in the incoming flow. For instance, this is discussed on the basis of comparison with highly resolved LES by Chang et al [2007] in their DES study of flow and contaminant ejection from a bottom river cavity. As the incoming flow in all applications of relevance to river engineering is turbulent and the flow predictions can be significantly affected by the characteristics of the incoming flow, it is important to specify inflow conditions that match as close as possible those present in experiments and in the field.…”
Section: Introductionmentioning
confidence: 99%